1993
DOI: 10.1037/0021-843x.102.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Perception of self and other in major depression.

Abstract: Previous research on the nature of person perception in depression has been inconclusive. This investigation differs from earlier studies in that extensive free-response descriptions of other people and self were collected from patients with major depression and from nonpsychiatric control Ss. In comparison with control Ss, depressed patients described fewer positive aspects not only of self but also of parents and significant others and reported more negative aspects of these people. Cluster analysis (HICLAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
3
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 47 publications
8
95
3
1
Order By: Relevance
“…The core of the personality trait neuroticism is conceptualized to be a sensitive to negative stimuli (Tellegen, 1985), thereby causing high trait scorers to experience a broad range of negative moods, including fear/anxiety, sadness/depression, guilt, hostility and self-dissatisfaction (Watson and Clark, 1984). A wide range of non-mood variables are related to this affective core, including negative cognitions (Clark et al, 1990), somatic complaints (Watson and Pennebaker, 1989) and negativistic appraisal of self and others (Gara et al, 1993). These characteristics form a highly pervasive dimension of subjective experience, and they are strongly related with the onset and course of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The core of the personality trait neuroticism is conceptualized to be a sensitive to negative stimuli (Tellegen, 1985), thereby causing high trait scorers to experience a broad range of negative moods, including fear/anxiety, sadness/depression, guilt, hostility and self-dissatisfaction (Watson and Clark, 1984). A wide range of non-mood variables are related to this affective core, including negative cognitions (Clark et al, 1990), somatic complaints (Watson and Pennebaker, 1989) and negativistic appraisal of self and others (Gara et al, 1993). These characteristics form a highly pervasive dimension of subjective experience, and they are strongly related with the onset and course of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Research on narcissism has documented systematic distortions in narcissists' selfperceptions (John & Robins, 1994), and analogous biases in perceiver effects may be an important part of the cognitive framework underpinning other forms of psychopathology. For example, distorted perceptions of others have been associated with both borderline personality disorder (Benjamin & Wonderlich, 1994), depressive disorder (Gara et al, 1993), and conduct disorder (Dodge, 1993). The finding that perceiver effects have a multidimensional structure may provide a framework for organizing this literature.…”
Section: Implications For Studying Interpersonal Functioning and Psycmentioning
confidence: 99%
“…A more nuanced approach, and one that accounts for the finding that perceiver effects are context dependent, would be to compare perceiver effects formed in relation to different sets of others across different contexts. For example, some research has suggested that depressed individuals might be more likely to use social projection, and therefore to form more negative perceptions of others, in contexts in which they feel close to or dependent on others (Gara et al, 1993). Similarly, the correlations between attachment style and perceiver effects might have been stronger in a context in which attachment concerns were more relevant and the attachment system was more highly activated, such as in groups of people who expected to rely on one another for acceptance and support.…”
Section: Implications For Studying Interpersonal Functioning and Psycmentioning
confidence: 99%
See 1 more Smart Citation
“…Gara, et al, 1987;Gara et al, 1989;Robey et al, 1989;Gara et al, 1993). In one cross-sectional study of non-clinical subjects aged 10-27 years, Haviland et al (1994) used HICLAS to study the place of emotion in the self-structure models of adolescents.…”
Section: Introductionmentioning
confidence: 99%